Stereostructure assignment of flexible five-membered rings by GIAO 13C NMR calculations: prediction of the stereochemistry of elatenyne. - Smith, S; Paton, R; Burton, J; Goodman, J (2008)
The stereochemistry of conformationally mobile five-membered rings is often hard to assign from NMR data, and [2,2']bifuranyl systems are even more challenging. GIAO (13)C NMR chemical shifts have been calculated for a series of [2,2']bifuranyl and pyranopyran species, taking into account their conformational flexibility using weighted averages of the data for all low energy conformers. We show that calculation of (13)C NMR chemical shifts using the geometries obtained using molecular mechanics greatly reduces the computational expense without a significant loss of accuracy, even in this demanding system. The results were sufficiently accurate to distinguish not only the pyran and furanyl isomers but also between all the diastereoisomeric forms. As a result of this validation, we predict the stereochemistry for the recently proposed revised structure of the natural product elatenyne, which contains a [2,2']bifuranyl core.